1992
DOI: 10.1002/1097-0355(199223)13:2<157::aid-imhj2280130206>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal loss and maternal attitudes toward the subsequent child

Abstract: Twenty‐five mothers who had experienced a previous perinatal loss and a comparison group of 30 nonloss mothers completed the Maternal Attitude Questionnaire (MAQ) and the Maternal Separation Anxiety Scale (MSAS) when their children were 16 months old. The purposes of the study were to describe and evaluate the development of a new measure (the MAQ) and to examine the hypothesis that mothers who experienced a perinatal loss would express (a) more concern about the subsequent child's health, (b) more investment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
1
19
0
1
Order By: Relevance
“…In one study, mothers of 16-month-old children born subsequent to perinatal loss reported that they were more concerned about the child’s health, and more concerned with the psychological separation between mother and child as the child developed [17]. However, in another study, Price [20] reported that mothers with a history of perinatal loss did not perceive their 9 month old child as more difficult to raise than other children.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, mothers of 16-month-old children born subsequent to perinatal loss reported that they were more concerned about the child’s health, and more concerned with the psychological separation between mother and child as the child developed [17]. However, in another study, Price [20] reported that mothers with a history of perinatal loss did not perceive their 9 month old child as more difficult to raise than other children.…”
Section: Discussionmentioning
confidence: 99%
“…The MAQ contains three subscales: concerns about the child's health, concern about differentiation from the child, and investment in the child. A previous Cronbach's a of .78 demonstrates good internal consistency (Theut et al, 1992). The concurrent validity of the instrument is supported by correlations with another measure of maternal separation anxiety (Maternal Separation Anxiety Scale) developed by Hock, McBride, and Gnezda (1989).…”
Section: Methodsmentioning
confidence: 99%
“…The concurrent validity of the instrument is supported by correlations with another measure of maternal separation anxiety (Maternal Separation Anxiety Scale) developed by Hock, McBride, and Gnezda (1989). Derivation of items from interviews with mothers of infants and toddlers who had experienced a prior perinatal loss and those with no history of loss as well as factor analysis supports the instrument's construct validity (Theut et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Prior pregnancy loss may also negatively impact subsequent pregnancy experiences, parenting, and child outcomes due to fear of another loss, anxiety during pregnancy and hypervigilance of living children (Blackmore et al, 2011; Côté-Arsenault, 2007; O'Leary and Warland, 2012; Theut et al, 1992). …”
Section: Pregnancy Lossmentioning
confidence: 99%